Biosynthesis of Lovastatin by Gamma Irradiated Aspergillus terreus (Journal of Nuclear Technology in Applied Science, 2021)
Lovastatin (C24H36O5, Mevinolin, Monacolin K and Mevacor®) is the first compound of its kind to become available for treatment of hypercholesterolemia. This fungal secondary metabolite is produced by Aspergillus, Monascus and Penicillium species, via the polyketide synthase (PKSs). The role of hypercholesterolemia as a risk factor for atherosclerosis, and ischemic heart disease was indicated by the clinical, epidemiologic and pathologic studies.In the present study, gamma irradiated of selected highly lovastatin producer Aspergillus terreus isolate (A. terreus S3γ8) was employed for lovastatin production in submerged fermentation (SmF) conditions. Different fermentation parameters including: incubation period, initial pH of the medium, temperature, different carbon and nitrogen sources, type of inoculum and agitation; were carried out under SmF conditions to enhance the lovastatin production. The maximum lovastatin production (547.33 mg/l) was achieved at initial pH 6, incubation temperature 30 °C, agitation rate 150 rpm, 4% soluble starch and 0.3% yeast extract as carbon and nitrogen sources, respectively, after 8 days when the production medium (which containing bio-elements: KH2PO4, MgSO4 and MnSO4) was inoculated with 48 h age from seed culture inoculum.
Keywords: Aspergillus terreus; Lovastatin; Submerged fermentation; Gamma radiation